FALLING HEAD (FH) UNTUK HUBUNGAN SIFAT BATUAN DENGAN KOEFISIEN KELULUSAN AIR DI DAERAH “BRG” SEKITARNYA - Rohima Sera Afifah (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2022)
The basalt of "Ohi" Mount and the Andesite Hornblend on "Ser" Mount are a barrier to the flow of groundwater from "Ifa" Mount. Both are an influence on the productivity aquifer. The characteristic of lithology in water is an influence of the permeability coefficient. Falling head is one of the methods of measuring the determination of coefficient permeability. Based on the location measurement, To know the units of rock formed, (2) To know the Productivity aquifer system (local, medium and small); (3) To know the coefficient permeability of characteristics of lithology. Coefficient of Permeability A stream is said to be good if the nature of the rock type has a positive result or the greater the water pass rate, and conversely, the passing value of a negative result has a very small water pass rate. Its goal was to determine the relationship between lithology characteristics and permeability coefficients in the "BRG" area and surroundings. The "BRG" area and its surroundings, based on the location point of measurement of the rock unit, were the Breccia Andesite Hornblend unit, The Medium Productivity Aquifer Dominated. The average coefficient of permeability (K) is 63,300 cm/day. The five location measurements were: 1 st area DS, S1, 2 nd DS area, S2, 3 rd DN area, 4 th DD area, and 5 th DR. The aquifer of the five locations had through fracture permeability and had a type of steep hill morphology